(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This research aims to determine the components of the transitivity system, namely processes, participants and circumstance which are used in the lyrics of the song "A Whole New World". This research was conducted because many listeners and users of this song do not know the meaning of the lyrics,. This research was conducted using a qualitative method, namely the method of collecting data by analyzing each clause in the lyrics. This research was collected by taking several steps, namely listening and reading the lyrics of the song first, and then analyzing each clause contained in the lyrics, and finally by identifying the use of the transitivity system components in the lyrics of the song "A Whole New World". The data from this study are sourced from lyric papers. So this study found the transitivity system components (Process, Participants and Circumstances) used in the lyrics of the song "A Whole New World". Where in the lyrics of the song is found the use of material, mental, relational (attributive and identifying), verbal, existential processes. Use of Participants namely actor, senser, carrier, token, sayer, existent, target, attribute, phenomenon, verbiage, value participants. And also the use of circumstances extent (temporal and spatial), location (temporal and spatial), contingency, accompaniment. So, it was found that the most dominant use of transitivity system components used was Process Material (48%), Participant Attribute (24%), and also Location Temporal circumstance (30%).